If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(9c + 8) = 26 Reorder the terms: -3(8 + 9c) = 26 (8 * -3 + 9c * -3) = 26 (-24 + -27c) = 26 Solving -24 + -27c = 26 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -27c = 26 + 24 Combine like terms: -24 + 24 = 0 0 + -27c = 26 + 24 -27c = 26 + 24 Combine like terms: 26 + 24 = 50 -27c = 50 Divide each side by '-27'. c = -1.851851852 Simplifying c = -1.851851852
| (A+2)0.78=3.9 | | 4(90-x)+2=(180-x)+8 | | C=X^2-15x+50 | | 3(x+5)=x-10 | | 3535x-5725x+58y=4734z | | a/4-3/4=1/3 | | y^2-12y+27= | | X^5-4x^4+7x^3-10x^2+10x-4=0 | | A=(7x)(3x) | | -7x-3=13 | | 9.5=0.4(5x)+2.5 | | 9x+1=5x+15 | | 7*y-3=2*y-3 | | x^2-10x+25=x^2-8x+16+1 | | (x-5)=(x-4) | | 10(2x-10)=0 | | 3*200=2+x | | ln(x+8)-ln(x-2)=ln(x+2) | | h=-16t^2+250 | | a-1=14 | | 2x-5=8x+7-4x | | 4(2z+1)-6=70 | | x^2-10x+25-1=0 | | 24x+3=51 | | 12x+6y=8 | | 9(z+1)-2(z-4)=3(z-2)+3(z-4) | | 25+5n=9(7n+4) | | 3x^2-22x+16=0 | | +2.25-13.5=9 | | 5x+2(y+8)=18 | | 10t-5+4t=10-t | | 10x-(5x-8)=33 |